Dithienonaphthalene-Based Non-fullerene Acceptors With Different Bandgaps for Organic Solar Cells - Zhang, Meiqi; Ma, Yunlong; Zheng, Qingdong (Frontiers in Chemistry, 2018)
Compared to the traditional fullerene derivatives, non-fullerene acceptors show more tunable absorption bands as well as adjustable energy levels which are favorable for further PCE enhancement of organic solar cells. In order to enhance light-harvesting property of dithienonaphthalene (DTN)-based acceptors, we designed and synthesized two novel non-fullerene acceptors (DTNIF and DTNSF) based on a ladder-type DTN donor core flanked with two different acceptor units. In combination with a benchmark wide bandgap copolymer (PBDB-T), the best performance device based on DTNIF displayed a high PCE of 8.73% with a short-circuit current (Jsc) of 13.26 mA cm-2 and a large fill factor (FF) of 72.77%. With a reduced bandgap of DTNSF, the corresponding best performance device showed an increased Jsc of 14.49 mA cm-2 although only a moderate PCE of 7.15% was achieved. These findings offer a molecular design strategy to control the bandgap of DTN-based non-fullerene acceptors with improved light-harvesting.